An Analysis of Flouting Maxims in TV Show Brooklyn Nine-Nine: Season 5 based on Pragmatics Approach - Subagyo, Zelin Feby Zeina (Universitas Sebelas Maret, 2022)
This aim of this article is to find out the types of flouting maxims employed by the characters in the television show Brooklyn Nine-Nine: Season 5, the way the speakers flout the maxims, and to explain the reasons of the characters in the show flout the maxims using pragmatics approach.This research was a descriptive qualitative research and used a total sampling technique. The data analyzed by the researcher are all the dialogues containing flouting maxims that were uttered by the main characters in the show.By applying Grice’s cooperative principles and his theory of flouting maxims, the researcher found 27 data in total of 22 episodes of the entire season. The result shows that the way the characters flout the maxims varies, but the maxim of quality is flouted the most to create humor.